Domestic Wounds: Nursing in Louisa May Alcott’s War tales - Daniela Daniele (European Journal of American Studies)
Louisa May Alcott’s literary career started with a humorous account of her nursing experience in the Union Army. The Civil War remained a major theme even in the tales that she wrote during the Reconstruction Era. They celebrate the professional achievements of sturdy “deaconesses” like Dorothea Dix, who rapidly turned the dilapidated sanitary system of a divided nation into a domestic order restored by female healing powers.